Microalgae Granulation Correlation Between Microalgae Growth And Eps Content - Halim, Farah Zahidah Abd (Universiti Sains Malaysia, 2022)
Microalgae are often used in biological wastewater treatment as it can survive harsh condition aside from being a potential alternative resource for biofuel production. However, there are slight disadvantages to both applications as the algae culture are mostly low in density and small in size. This results in rigid separation process which requires greater cost in harvesting and separation processes. Nonetheless, microalgae are able to produce extracellular polymeric substances (EPS) which is significant for the granule formation. By supplying cultural condition that is suitable for microalgae to form granule, the process of harvesting and separation of microalgae will be much secure as granule has higher density and can settle down easily. In this experiment, several factors that influence the production of extracellular polymeric substances (EPS) by microalgae are studied, which are the availability of nutrient and growth phase of the microalgae. MLSS, EPS content and nutrient analysis are carried out periodically throughout the experiment. There is formation of granular sludge in microalgae found after the growth of microalgae reach stationary phase.